(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Chronic arterial hypertension in pregnant women is one of the leading causes of maternal and perinatal complications, including preeclampsia, placental insufficiency, and preterm birth. Despite advances in modern medicine, the risk of adverse outcomes in this group of patients remains high. The lack of unified prognostic criteria for complicated pregnancy necessitates the identification of significant risk factors and the development of early prediction methods to optimize preventive and therapeutic strategies.